From Conservative Turn to Non-Violence Politics: Theo-Politik Salib John Howard Yoder - Andreas Kristianto (Sekolah Tinggi Teologi Intheos Surakarta, 2020)
Abstract. The Reformation era was recorded as an era of democracy that was marked by various violence acts in the name of religion. This violence was caused by the rise of religious conservatism (conservative turn). In this context, the writer wants to offer an alternative solution through the theo-politics of the cross of John Howard Yoder, a US Mennonite figure. The result of this study was that the theo-politics of the cross builds a consciousness that can counter the consciousness that comes from religious conservatism, but by means of non-violence. The theo-politics of the cross builds an alternative community that shows a friendly face of the church and solidarity with the marginal people.Abstrak. Era Reformasi tercatat sebagai era demokrasi yang diwarnai dengan berbagai tindak kekerasan atas nama agama. Kekerasan atas nama agama ini disebabkan oleh bangkitnya konservatisme agama (conservative turn). Dalam konteks ini, penulis hendak menawarkan solusi alternatif melalui theo-politik salib John Howard Yoder, seorang tokoh Mennonite Amerika Serikat. Hasil dari kajian ini adalah bahwa theo-politik salib membangun suatu kesadaran yang dapat melawan kesadaran yang bersumber pada paham konservatisme agama, namun dengan jalan tanpa kekerasan. Theo-politik salib membangun komunitas alternative yang menampilkan wajah gereja yang ramah, dan solider terhadap kaum marjinal.